Dengue With Scrotal Swelling: Rare Case Report - Mahbub Mayukh Rishad; Saha, Pradiptha; Khan, Rohit; Zahiruddin, Mohammad (Bangladesh Journal of Medicine, 2024)
Dengue fever is a mosquito-borne illness that occurs in tropical and subtropical areas of the world. Dengue fever (DF) is transmitted by Aedes aegypti mosquitoes. With rising disease burden, atypical manifestations have increased as well. We report a case of Dengue fever with acute scrotal swelling. Through detailed history, examinations, investigations including imaging, we confirmed the diagnosis and effectively excluded other possible reasons. Ultimately the swelling got resolved and patient was discharged uneventfully. By examining these cases, we aim to improve awareness of this under-recognized complication and guide healthcare professionals in its diagnosis and treatment. Bangladesh J Medicine 2025; 36: 64-65